Scoping review of health in office design approaches. Issue 2 (16th March 2020) - Forooraghi, Melina; Miedema, Elke; Ryd, Nina; Wallbaum, Holger
Abstract : Purpose: This paper aims to explore the literature on office design approaches (ODAs) in relation to employee health. The overall goal is to facilitate the practical use and theoretical development of design approaches to healthy offices. Design/methodology/approach: A scoping review of 7, 432 papers collected from 4 electronic databases and 5 scientific journals resulted in the selection of 18 papers for content analysis. Findings: Various ODAs relating to building design features and health were identified. The findings highlight challenges for this emergent field, including a paucity of literature on ODAs, a lack of definitions of health and healthy offices, ambiguous design strategies and a lack of a holistic ODA. Originality/value: ODAs are potentially valuable resources but an under-considered topic for healthy office development. To the best of the authors' knowledge, this study is the first scoping review to map and compare different design approaches in the context of office design and its main contribution is in encouraging researchers and practitioners to bring a salutogenic and holistic perspective to their design approaches.